FEATURES THE INFLUENCE OF PERSONALITY TRAITS ON PROFESSIONAL BURNOUT WITH PROLONGED COUNSELING - Khosravi , V. (Modern Psychology, 2019)
The problem of professional burnout in recent times is very relevant and attracts the attention of psychologists. Transformations of the modern world in the field of professional activity change the attitude of people to work, workloads have increased, employees lose confidence in the stability of their social and material status, in long-term job preservation, material benefits, and competition for prestigious and wellpaid work intensifies.journals.ysu.am/index.php/actual-psychology/submission/wizard/2?submissionId=5105#step-2